The growing digital divide in Europe and the United States - Désirée Rückert; Reinhilde Veugelers; Christoph Weiss (European Investment Bank (EIB), 2020)
Using a new survey on digitalisation activities of firms in the EU and the US, we identify digitalisation profiles based on the current use of digital technologies and future investment plans in digitalisation. Our analysis confirms the trend toward digital polarisation and a growing digital divide in the corporate landscape with, on one side, many firms that are not digitally active, and on the other side, a substantial number of digitally active firms forging ahead. Old small firms, with less than 50 employees and more than 10 years old, are significantly more likely to be persistently digitally non-active. We show that these persistently non-digital firms are less likely to be innovative, increase employment or command higher mark-ups. These trends are likely to exacerbate the digital divide across firms in the EU and the US.
Keywords: D22; E22; L25; 330; digital technology; investment; firm performance